2005
DOI: 10.2174/1570162053506900
|View full text |Cite
|
Sign up to set email alerts
|

Non-Replicating Viral Vector-Based AIDS Vaccines: Interplay Between Viral Vectors and the Immune System

Abstract: During the past 20 years, the development of HIV vaccines has come a long way. The focus has progressively changed from the traditional protein-based HIV vaccines that induce humoral immunity to the live recombinant viral vector-based HIV vaccines capable of eliciting both cellular and humoral immune responses. These new viral vector-based vaccines encoding multiple HIV antigens, delivered either alone or in heterologous prime-boost modalities elicited antigen-specific CTL responses in immunized hosts and prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 232 publications
(293 reference statements)
0
6
0
Order By: Relevance
“…Therefore, they are harmless. Besides, they elicit an immune response higher than viral protein-based vaccines [201] , [202] , [203] .…”
Section: Development Of Covid-19 Vaccinesmentioning
confidence: 99%
“…Therefore, they are harmless. Besides, they elicit an immune response higher than viral protein-based vaccines [201] , [202] , [203] .…”
Section: Development Of Covid-19 Vaccinesmentioning
confidence: 99%
“…They can potentially produce strong immunogenic responses. 64,65,228 COV2.S (Janssen [Johnson & Johnson]), AZD1222 (Oxford/AstraZeneca) and Sputnik Light (Gamaleya) are approved for use, but trials of AdCOVID (Altimmune Inc.) are no longer in progress due to its lower effectiveness. 47 Still, some of these vaccines are in the developmental stages.…”
Section: Clinical Status Of Non-replicating Viral Vector Vaccines Aga...mentioning
confidence: 99%
“…Additionally, prime-boost strategies of viral vectors had shown promising results. Many viral vector-based HIV vaccine candidates are under clinical and preclinical investigation, including adenovirus, poxvirus, alpha virus, and adenoassociated virus, in addition to combination of viral vectors encoding HIV gene (Sauter et al, 2005). For the first time, RV-144 in a phase III efficacy clinical trial in Thailand had shown that HIV infection can be prevented by vaccination.…”
Section: Aidsmentioning
confidence: 99%